LocaLibras: An Inclusive Geolocation Application - Pimentel, Samara Fernandes; Ferreira, Paulo Weskley de Almeida; Teran, Luciano; Mota, Marcelle (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
The Brazilian sign language (Libras) is, by law, the second official language of the country. However, a large part of the listeners do not know it. The lack of knowledge of Libras by listeners and the Portuguese language by deaf damages communication between them. The existing computational applications concentrate on the translation of the two languages and disregard regionalization. Besides, they do not promote the independence of the deaf. In this paper, a multiplatform application is presented that helps the deaf to relate places with their signs in Libras, also facilitating their journey with the use of routes.We carried out a study with people who understood Libras, including evaluation, observation, and interviews. The results obtained enabled the perception of problems that negatively affected the use of the application and served to signal improvements in interaction. We believed that the study would allow the appropriation of knowledge discovered in other contexts of use.